2009
DOI: 10.1002/jca.20208
|View full text |Cite
|
Sign up to set email alerts
|

LDL lipid apheresis rapidly increases peripheral endothelial progenitor cell competence

Abstract: Patients with refractory hyperlipidemia exhibit lower peripheral EPC numbers and a lower proliferative activity of circulating EPCs than healthy controls. A single lipid apheresis treatment significantly stimulates EPC proliferation, it furthermore increases cellular eNOS. In summary, these results show that lipid apheresis mediates beneficial effects on the EPC system as an essential element in the process of vascular repair in the human organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…For analyzing apoptosis, the percentage of Annexin V ϩ cells was quantified using a commercially available kit (BD, Heidelberg, Deutschland) according to the manufacterer's protocol. Necrosis was simultaneously measured by cytometric analysis as described previously (26). Briefly, cells with positive uptake of propidium iodide (PI) and positive staining of Annexin V were defined as apoptotic/necrotic.…”
Section: Methodsmentioning
confidence: 99%
“…For analyzing apoptosis, the percentage of Annexin V ϩ cells was quantified using a commercially available kit (BD, Heidelberg, Deutschland) according to the manufacterer's protocol. Necrosis was simultaneously measured by cytometric analysis as described previously (26). Briefly, cells with positive uptake of propidium iodide (PI) and positive staining of Annexin V were defined as apoptotic/necrotic.…”
Section: Methodsmentioning
confidence: 99%
“…As statins reduce LDL oxidation, it may also protect EPCs from toxic oxidized LDL that leads to increased cell senescence and EPC dysfunction (43). Recent findings also demonstrated that LDL reduction by lipid apheresis in patients with refractory hyperlipidaemia increases EPC function (66).…”
Section: Statinsmentioning
confidence: 95%
“…OxLDL treatment reduces eNOS expression both in mature endothelium (102) and EPC, which resulted in decreased EPC survival and impaired adhesive properties (61). Likewise, LDL lipid apheresis increased peripheral EPC function in patients with refractory hyperlipidemia (66). Physical activity upregulates eNOS expression in EPC isolated from the spleen and bone marrow of mice (57).…”
Section: Fleissner and Thummentioning
confidence: 99%
“…The improvement of endothelial function associated with statin use is directly correlated with the increase in EPC numbers and measures of EPC function (Higashi, Matsuoka et al 2010). Similarly, lipid apheresis for resistant hypercholesterolemia improves EPC function and mobilization (Patschan, Patschan et al 2009;Ramunni, Brescia et al 2010). Low high density lipoprotein cholesterol (HDL-C) has been identified as secondary therapeutic target and reconstituted HDL-C infusion improves endothelial function and raises EPC numbers (Nieuwdorp, Vergeer et al 2008).…”
Section: Dyslipidemiamentioning
confidence: 99%